2019
DOI: 10.1155/2019/5935279
|View full text |Cite
|
Sign up to set email alerts
|

Short-, Mid-, and Long-Term Effect of Granulocyte Colony-Stimulating Factor/Stem Cell Factor and Fms-Related Tyrosine Kinase 3 Ligand Evaluated in an In Vivo Model of Hypoxic-Hyperoxic Ischemic Neonatal Brain Injury

Abstract: Hematopoietic growth factors are considered to bear neuroprotective potential. We have previously shown that delayed treatment with granulocyte colony-stimulating factor (G-CSF)/stem cell factor (SCF) and Fms-related tyrosine kinase 3 ligand (FL) ameliorates excitotoxic neonatal brain injury. The effect of these substances in combined-stressor neonatal brain injury models more closely mimicking clinical conditions has not been investigated. The aim of this study was to assess the short-, mid-, and long-term ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…Hence, both G-CSF and SCF may work synergistically in improving the overall outcome of neonatal HI brain damage. Caspase-3 activation is reduced when G-CSF and SCF treatment are combined resulting in decreased apoptotic cell death, though other studies further reported that G-CSF/SCF and FL treatment did not affect apoptosis-inducing factor-dependent apoptosis or cell proliferation, and thus does not convey neuroprotection in neonatal HIE [ 112 , 113 ]. Indeed, there are mixed reports about the neuroprotective effect of combinational G-CSF and SCF treatment in neonatal HI-induced brain injury.…”
Section: Combinational Therapy With Other Agentsmentioning
confidence: 99%
“…Hence, both G-CSF and SCF may work synergistically in improving the overall outcome of neonatal HI brain damage. Caspase-3 activation is reduced when G-CSF and SCF treatment are combined resulting in decreased apoptotic cell death, though other studies further reported that G-CSF/SCF and FL treatment did not affect apoptosis-inducing factor-dependent apoptosis or cell proliferation, and thus does not convey neuroprotection in neonatal HIE [ 112 , 113 ]. Indeed, there are mixed reports about the neuroprotective effect of combinational G-CSF and SCF treatment in neonatal HI-induced brain injury.…”
Section: Combinational Therapy With Other Agentsmentioning
confidence: 99%